FORECASTING OF MAXIMALLY ADMISSIBLE POTENTIALS OF THE STATIC ELECTRICITY CATEGORIES AND THEIR INFLUENCE TO THE SHOTTKI DIODES - V. A. Soloducha; V. L. Lanin; Y. A. Solov'yov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The forecasting technique of admissible potentials of the static electricity categories of positive and negative polarity with voltage to 15 kV on structures of diodes Shottki with the guard ring is offered.